Wing Morphology and Echolocation of Rhinopoma hardwickii (Lesser Mouse-tailed Bat, Gray, 1831) - Singh, Shaktivardhan; Elangovan, Vadamalai; Bharti, Sanjay Kumar; Misra, Pawan Kumar (Malaysian Journal of Science, 2024)
Rhinopoma hardwickii is currently classified as a member of the Yinpterochiroptera suborder, which includes frugivorous and some insectivorous bats. This species is the smallest in the Rhinopomatidae family and easily identified by its long tail. The wing morphology and echolocation calls of this species were studies to see if there were any changes in wing morphology between sexes, echolocation calls across different environments such as natural (roost and field) and controlled (captive), as well as different geographical areas. In this study, a total of 41 individuals (27 male and 14 female) of R. hardwickii were captured and their wing morphology was measured. The results show that there were no statistically significant variations in their morphometric characteristics or in wing morphology between the sexes. This species has with high wing loading and a high aspect ratio, as well as pointed wing tips. The echolocation calls consisted up to five harmonics of FM and CF- FM sweeps. Peak frequencies, start frequency, end frequency, and IPI of three separate environment parameters (roost, capitative, and field recording) differed significantly (p > 0.001).Moreover, we compared the frequency at maximum energy with four different geographical regions such as Kerala, Gujrat, and Israel to current study, and found that the frequencies of bat calls do not vary with geographical region (H=0.667, df=3, p=0.881). Therefore, the current study provides accurate identification of R. hardwickii on the basis of echolocation call in a different environment. The echolocation call and wing morphology data clearly show that this species is a fast flyer with limited manoeuvrability that feeds on forest canopy or over water bodies.